Impact of Liquidity Management on Profitability of Joint Venture Commercial Banks in Nepal (The Lumbini Journal of Business and Economics, 2023)
This study investigates the Impact of Liquidity Management and Profitability of Joint Venture Commercial Banks in Nepal. Data analysis was done using descriptive statistics, Pearson correlation, regression analysis, and t-test. The data used to analyze five (5) samples size, out of 27 which has found to be covering period 2012-2021 of joint venture commercial Banks in Nepal. The Liquidity management represents the variables of the Credit Deposit Ratio (CDR), Capital adequacy ratio (CAR), Current Reserve ratio (CRR), Total deposit to total ratio (TDTAR), Total loan to total assets ratio (TLTAR) and the profitability including Return on Assets (ROA). The findings of the study have a R square value of 0.615 meaning that 61.5% of the variation in the dependent variable is explained by the independent variables while 38.5% is explained by other variables outside the model and also showed that there is a strong positive correlation between the dependent variable and the set of independent variables. The result showed that there is significant impact of TLTAR on ROA and there is insignificant impact of CDR, CAR, CRR and TDTAR on ROA of joint venture commercial banks in Nepal.